If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2) = x + 12 Reorder the terms for easier multiplication: 2x = x + 12 Reorder the terms: 2x = 12 + x Solving 2x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 12 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 12 + x + -1x Combine like terms: x + -1x = 0 1x = 12 + 0 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 5-y=17 | | 16x+4+3x+11=110 | | 16x+4+3x+11= | | 3(2x-1)-8=13 | | (x-5)(x(2)+5x)= | | (x+1)*(1+a)=2ax-a(x-3) | | (6+9i)+(-5+i)= | | (x-5)(2)=4 | | x(2)-13x+36= | | 10x+7-6*(x-1)=3*(x+3) | | 0.3x-0.3(5)=0.6 | | 2x-3(4x+7)=0 | | 2x+41000= | | 0.1(50)=0.4(70+x)-0.6x | | (5v^2)+6=17v | | 1.9x-3.1-(0.9x+4)=-1.8 | | 3+5(s-4t)=8s-32t | | 75(x+4000)=80x+50(1000) | | 23x+69=9000000 | | 23x+69=9 | | 23x+69=90 | | 23x+69=906 | | z^6+2z^3+2=0 | | 3x+y+4z=-12 | | 3e+2=3e+2(e-2) | | -x+1=1+4x | | x+5y+10=0 | | 4x^3*y+3y^2=4y^3*x+3x^2 | | 5x+7(2x+41000)= | | 7X-(3X-5)=29 | | 8(4x-5y)-7(7x+6y)= | | -2.5(-2+.4y)+y=5 |